Desenvolvimento de pão de queijo sem lactose e análise da influência deste carboidrato em sua composição - Barbosa, Ana Laura Paula Barros (Universidade Federal de São Carlos, 2023)
The cheese bread is a traditional product from Minas Gerais (MG) that is currently consumed and produced in all regions of Brazil. Traditionally, it is made from milk, starches, cheese, eggs and salt. The objective of the project was to produce lactose-free cheese bread and to analyze the influence that the absence of this carbohydrate causes on the chemical and physical characteristics of the product. In addition, it was intended to deepen the knowledge about cheese bread, since it does not have a standard of identity and quality that defines it. Different formulations of cheese breads, with and without lactose, produced in the Sabor Supremo industry and frozen food trade, located in Boituva-SP, were analyzed regarding their centesimal composition. The moisture content of cheese bread without lactose was higher than that of traditional cheese bread, corresponding to 44% and 46%, respectively. The fixed mineral residue content was close for both formulations, being 1.9% for the lactose-free samples and 2.1% for the traditional samples. Regarding the protein content, the lactose-free formulation had 1.92% while the traditional one had a content of 2.55%. For the lipid content, 22% was obtained for the lactose-free cheese breads and 21% for the traditional cheese breads. Finally, the texture of the cheese bread was also analyzed using a texturometer, which indicated the maximum compression force for the samples, obtaining an equivalent force of 0.67 N for traditional cheese breads and 1.40 N for lactose-free cheese breads. In this way, it is possible to conclude that cheese breads with and without lactose have similar physicochemical characteristics.
Development of lactose-free cheese bread and analysis of the carbohydrate influence on its composition
Keywords: Pão de queijo; Lactose; Padrão de identidade e qualidade; Composição centesimal; Textura; Cheese bread; Lactose; Identity and quality standards; Centesimal composition; Texture; CIENCIAS AGRARIAS::CIENCIA E TECNOLOGIA DE ALIMENTOS